Factors and Pathways to Enhance Resident Satisfaction in Old Residential Neighbourhood Renovation: A Configuration Analysis of Cases in Central Nanchang, China - Haifang He; Hongrui Wang; Lin Zheng; Tengfei Zhao; Puwei Zhang; Kan Zheng (Buildings)
The renovation of old residential neighbourhoods represents a critical livelihood initiative. In this study, a theoretical framework utilising fuzzy-set qualitative comparative analysis (fsQCA) is developed to investigate the complex interplay of factors influencing residential satisfaction and to identify multiple pathways for satisfaction enhancement in old residential neighbourhood renovation projects. Thirty old residential neighbourhoods within Nanchang’s urban core are selected as case studies. Through the systematic evaluation and measurement of five critical dimensions—governmental policy; community environment; community support; housing quality; and resident perception—the research applies fsQCA to analyse potential pathways for enhancing residential satisfaction from a “community” perspective. The research finds that residents’ satisfaction can be enhanced through four pathways: housing quality enhancement, quality and support improvement, community environment improvement, and environment–quality linkage. The research findings yield key policy implications: First, a multifactorial synergistic approach should be implemented to overcome reductionist tendencies toward single-factor solutions. Second, differentiated rehabilitation frameworks should be developed to prevent homogenisation in old residential neighbourhood renovation practices. Third, enhancing the accessibility and comprehensibility of government policies through effective communication strategies is crucial, and cultivating a community ethos centred on co-creation, co-governance, and shared benefits should be prioritised to foster collective responsibility and participatory decision-making.